Preparation of student activity sheets results of research on the effect of crude bacillus subtilis enzyme concentration on sugar and ethanol content from sugarcane bagasse fermentation using zymomonas mobilis as biology teaching materials - Widyaningrum, Trianik; Pertiwi, Hana Eka; Utami, Listiatie Budi (Universitas Ahmad Dahlan, 2024)
Student Activity Sheets (SAS) are teaching materials that are systematically and interestingly arranged in the learning process. In this case, the results of the study are used as material for compiling SAS. The study aims to determine the potential of SAS teaching materials from the results of the study on the effect of crude Bacillus subtilis enzyme concentration on sugar and ethanol content from bagasse fermentation using Zymomonas mobilis , the effect of crude Bacillus subtilis enzyme concentration on sugar and ethanol content from bagasse fermentation using Zymomonas mobilis , and the concentration of crude Bacillus subtilis enzyme that has the most influence on sugar and ethanol content from bagasse fermentation using Zymomonas mobilis . The research was conducted in 2 stages, the first was an experimental study conducted using a Completely Randomized Design (CRD) with the independent variable being the concentration of crude Bacillus subtilis enzyme, namely 0; 2.5; 5; 7.5; 10; 12.5; 15; 17.5% and the dependent variable being the sugar and ethanol content of the fermented sugarcane bagasse using Zymomonas mobilis . Measurement of sugar content used the DNS method, while measurement of ethanol content used an alcohol meter. Second, the preparation of SAS used the ADDIE development model which was modified to ADDE. The data from the experimental research results were analyzed using the One Way ANOVA test, while the preparation of SAS was analyzed using quantitative descriptions.. The results of the study showed that the SAS results of the study on the sugar and ethanol content of the results of the study of sugarcane bagasse using Zymomonas mobilis were categorized as very good to be used as teaching materials for biotechnology materials. The concentration of crude Bacillus subtilis enzyme that had the most influence on the sugar and ethanol content of the fermentation results of sugarcane bagasse using Zymomonas mobilis was in treatment 4 with a concentration of 10%, namely 0.67 g/mL and the highest ethanol content, namely 1.89%.